Model-assisted ultrasonic calibration using intentionally embedded defects for in-process weld inspection. (15th January 2021) - Mohseni, Ehsan; Javadi, Yashar; Sweeney, Nina E.; Lines, David; MacLeod, Charles N.; Vithanage, Randika K.W.; Qiu, Zhen; Vasilev, Momchil; Mineo, Carmelo; Lukacs, Peter; Foster, Euan; Pierce, S. Gareth; et al.
Abstract: Automated in-process Non-Destructive Testing (NDT) systems are rapidly gaining traction within the manufacturing industry as they reduce manufacturing time and costs. When considering calibration and verification of such systems, creating defects of known geometry and nature during the deposition of a weld can: (I) help examine the capability of the automated system to detect and characterise defects, (II) be used to form a database of signals associated with different defect types to train intelligent defect classification algorithms, and (III) act as a basis for in-process gain calibration during weld inspection at high temperatures, where the ultrasound beam can be skewed as a result of velocity gradients. In view of this, this paper investigates two unique methodologies for introducing: (a) lack of fusion weld defects by embedding tungsten in the weld and (b) creating artificial weld cracks by quenching to imitate the real cracking scenarios. According to the results of Phased Array Ultrasound Testing (PAUT) inspections, the methodologies used for embedding the artificial defects were successful. The validity of inspections was also verified by extracting micrographs from the defective sections of the welds, and model-based simulations were carried out to gain a better understanding of the wave propagation path and interaction with the generated defects. Graphical abstract: Unlabelled Image Highlights: Tungsten tubes could be successfully used for reference amplitude and gain calibration purposes. CIVA as a simulation tool was found to provide reliable predictions for the weld inspections. Local inter-pass water quenching of the weld can introduce cracks in the weld. Water quenching-induced cracks and tungsten inclusions can be successfully detected by phased array ultrasound.